2013
DOI: 10.5603/cj.a2017.0128
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of cutting balloon angioplasty for the treatment of congenital heart defects

Abstract: Cutting balloon angioplasty is a feasible and effective treatment option in different con-genital heart defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Prior studies have demonstrated significant increases in the minimal luminal diameter immediately post-CBA as well as shortterm follow-up. [3][4][5][6]9 Rothman et al reported 50% success in initial CBA, and 16% restenosis rate to the predilation diameter at a mean follow-up time of 10 months. 15 Bergersen et al demonstrated a nearly 150% mean increase immediately following CBA, though a 21% restenosis rate at a median follow-up time of 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies have demonstrated significant increases in the minimal luminal diameter immediately post-CBA as well as shortterm follow-up. [3][4][5][6]9 Rothman et al reported 50% success in initial CBA, and 16% restenosis rate to the predilation diameter at a mean follow-up time of 10 months. 15 Bergersen et al demonstrated a nearly 150% mean increase immediately following CBA, though a 21% restenosis rate at a median follow-up time of 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated significant increases in the minimal luminal diameter immediately post‐CBA as well as short‐term follow‐up 3–6,9 . Rothman et al reported 50% success in initial CBA, and 16% restenosis rate to the predilation diameter at a mean follow‐up time of 10 months 15 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations